Temporary reinforcement method for wooden cultural relics by using menthol and derivatives thereof

By performing specific reinforcement treatment on menthol and its derivatives, the problem that the reinforcement effect is affected by temperature and volatility process is solved, and the stable formation and easy removal of reinforcement layer are achieved, which significantly improves the strength and storage life of wooden cultural relics. , and maintain the original appearance of the cultural relics.

CN119266008APending Publication Date: 2025-01-07SHAANXI UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411560583.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

When existing menthol and its derivatives are used as temporary reinforcers to reinforce wooden cultural relics, the reinforcement effect is easily affected by improper control of temperature, environment and volatilization process, resulting in unstable reinforcement performance.

Method used

The wood matrix of different degradation degrees is reinforced by menthol or its derivatives. The wood blocks are cut and soaked in alkaline solution and then cooled, wrapped with fiber fabric and applied melted solidifier, and then covered with anhydrous ethanol degreased cotton. To completely remove the reinforcement, ensure the stability and easy removal of the reinforcement.

Benefits of technology

The tight combination of reinforcement and wood fibers has been achieved, which significantly improves the strength and stability of wood, extends the preservation life of cultural relics, and maintains the original appearance and authenticity of cultural relics through simple removal treatment, avoiding the reinforcement treatment belt Secondary damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119266008A_ABST
    Figure CN119266008A_ABST
Patent Text Reader

Abstract

The invention provides a method for temporarily reinforcing wooden cultural relics through menthol and derivatives thereof, and belongs to the field of cultural relic protection and wood processing. According to the method, healthy pine wood serves as a raw material, aged and degraded wood with moderate and severe degradation degrees is artificially prepared through a hydrothermal method, the wood with different degradation degrees is reinforced by adopting menthol and menthyl lactate serving as a derivative of menthol as a reinforcing agent, and the state of the wood before and after reinforcement is evaluated; and different protection modes of the aged wood with different degradation degrees are provided, so that the wood with different degradation degrees can be protected in time. The method has good simulated aging and degradation conditions, and the reinforcing mode is simple, effective, safe and environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of cultural relic protection and wood processing, and in particular relates to a method for reinforcing wooden cultural relics by using menthol and derivatives thereof. Background Art

[0002] As an important part of historical and cultural heritage, wooden cultural relics are very susceptible to factors such as humidity changes, light, and microbial erosion due to long-term exposure to the natural environment, resulting in varying degrees of aging, cracking, deformation, and decay. When these cultural relics are unearthed, they will be aged and degraded to varying degrees inside, and direct extraction will destroy the morphology and value of the cultural relics. This degradation process is complex and diverse, and the degree of degradation of cultural relics in different environments varies significantly, which poses a huge challenge to cultural relic protection. There are currently three main types of temporary solid protection materials commonly used: gypsum, polyurethane foam, and cyclododecane. Gypsum, whose main component is calcium carbonate, will form a white solid after solidification at room temperature. This solid has a certain hardness, but due to its high hardness after solidification, it is necessary to use saws, scalpels and other tools during the removal process. This operation is not only time-consuming and laborious, but may also cause secondary damage to the cultural relics, such as scratches and cracks. Polyurethane foam is used as a temporary solid material at archaeological excavation sites. Compared with gypsum, it has the advantages of small mass, low thermal conductivity, simple construction process, fast foaming and good shockproof effect. However, polyurethane foam also has some obvious disadvantages, especially the health risks associated with one of its components, isocyanate. Cyclododecane, as a waxy solid, has the advantages of high hydrophobicity, stable chemical properties, and slow sublimation at room temperature, but it has poor permeability, low adhesion, and certain flammability.

[0003] At present, there are various reinforcement technologies for wooden cultural relics, including physical reinforcement, chemical reinforcement and biological reinforcement. Among them, chemical reinforcement is widely used because of its simple operation and remarkable effect. Menthol, also known as menthol, is a compound found in the stems and leaves of mint, a plant of the Lamiaceae family, in nature. Menthol and its temporary solid protection material, which is natural, easy to obtain and has excellent performance, have broad application prospects at archaeological excavation sites. Its good solid strength, room temperature sublimation characteristics and permeability make it a powerful tool for protecting cultural relics.

[0004] However, in the existing process of using menthol and its derivatives as temporary reinforcement agents to reinforce wooden cultural relics, the reinforcement effect is easily affected by the temperature and humidity of the reinforcement object and the reinforcement environment, and the reinforcement effect of menthol and its derivatives is often affected by improper control of the volatilization process, and the reinforcement performance is unstable. Summary of the invention

[0005] In order to overcome the existing defects, the present invention provides a temporary reinforcement method for wooden cultural relics using menthol and its derivatives.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The first object of the present invention is to provide a temporary reinforcement method for wooden cultural relics using menthol and its derivatives, which specifically comprises the following steps: (1) Preparing wood substrates with different degradation degrees: cutting wood blocks, soaking the cut wood blocks in an alkaline solution, heating and keeping them warm, and then cooling them to room temperature for washing; (2) Reinforcement treatment of wood substrates with different degradation degrees using menthol or menthol derivatives as reinforcing agents: Wrapping the wood substrate obtained in step (1) with fiber fabric, applying a molten curing agent to the wrapped wood substrate, and obtaining a reinforced wood substrate sample after standing; (3) Removal of the reinforcing agent on the wood matrix: Cover the sample with cotton wool soaked in anhydrous ethanol and continuously replace the cotton wool with anhydrous ethanol. During this period, add water to the sample until the reinforcing agent is completely removed.

[0007] Preferably, in step (1), the reaction system is placed in a heating chamber for heating, and the temperature in the heating chamber is raised to 170-190° C. and maintained for 8-12 h.

[0008] Preferably, the alkaline solution in step (1) is a sodium hydroxide solution.

[0009] Preferably, the concentration of the alkaline solution in step (1) is 1-5%.

[0010] Preferably, in step (1), the wooden block is cut into cubes of 2×2×2 cm.

[0011] Preferably, the menthol derivative in step (2) is menthyl lactate.

[0012] Preferably, the application method in step (2) is any one of dripping, spraying and pouring.

[0013] Preferably, the water replenishment in step (3) is carried out by any one or more of spraying, steaming or immersing.

[0014] The second purpose of the present invention is to disclose the application of the temporary reinforcement method of menthol and its derivatives to wooden cultural relics in the field of wooden cultural relics reinforcement.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention adopts menthol and its derivatives as reinforcing agents, which can penetrate into the interior of wood, closely combine with wood fibers, and form a stable reinforcing layer. This reinforcing layer can significantly improve the strength and stability of wood, reduce deformation, cracking and other problems caused by natural aging, microbial erosion and other factors, thereby extending the preservation life of cultural relics, has the advantages of good volatility, fast curing, easy removal, etc., can effectively reinforce wood with different degrees of degradation, can be widely used in the field of preservation and restoration of historical cultural relics, and the materials used in the reinforcement process are all environmentally friendly reagents. After the reinforcement is completed, the reinforcing agent can be completely removed by simple removal treatment, which will not cause long-term effects on the wood, and is helpful to maintain the original appearance and authenticity of the cultural relics, and avoid changing the historical traces and style of the cultural relics due to the reinforcement treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Comparison of fresh pine wood and pine wood after hydrothermal degradation, a) initial healthy pine wood sample, b) 1% NaOH hydrothermal degradation, c) 5% NaOH hydrothermal degradation; Figure 2 Ultra-depth comparison of pine wood with different hydrothermal degradation degrees, a), b), c) pure water-hydrothermal; d), e), f) 1% NaOH-hydrothermal; g), h), i) 5% NaOH-hydrothermal; Figure 3 SEM comparison of pine wood with different hydrothermal degradation degrees, a) pure water-hydrothermal; b) 1% NaOH-hydrothermal; c) 5% NaOH-hydrothermal; Figure 4 FTIR spectra of pine wood treated by hydrothermal degradation and 85℃ water bath treatment; Figure 5 XRD patterns of pine wood treated by hydrothermal degradation and 85℃ water bath treatment; Figure 6 The super depth of field comparison diagram of the tangential direction of the pine wood samples after reinforcement and drying, a) and d) are fresh pine wood, b) is the pine wood after the menthyl lactate reinforcement agent is removed, c) the pine wood dried after the menthyl lactate reinforcement agent is removed, e) is the pine wood after the menthol reinforcement agent is removed, and f) the pine wood dried after the menthol reinforcement agent is removed; Figure 7 The process diagram of reinforcement and removal of water-saturated pine wood, a) water-saturated aged wood, b) water-saturated aged wood wrapped in gauze, c) water-saturated aged wood after the reinforcement agent is applied, d) water-saturated aged wood after the reinforcement agent solidifies, e) water-saturated aged wood after the reinforcement agent is applied covered with anhydrous ethanol absorbent cotton, f) the sample after removal; Figure 8Comparison of pine wood samples before and after reinforcement with 1% NaOH hydrothermal aging, a) before menthyl lactate reinforcement, b) after menthyl lactate reinforcement, c) before menthol reinforcement, d) after menthol reinforcement; Fig. 9 Comparison of pine wood samples aged with 5% NaOH hydrothermal treatment before and after reinforcement. a) before menthyl lactate reinforcement, b) after menthyl lactate reinforcement, c) before menthol reinforcement, and d) after menthol reinforcement. DETAILED DESCRIPTION

[0017] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0018] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0019] The present invention is further described in detail below in conjunction with the accompanying drawings: Preparation of the subject matter: Pine wood with different degrees of degradation was artificially prepared. The specific steps are as follows: select healthy pine wood with good quality, clear stripes and no defects (fresh wood with an initial moisture content of about 11%), and cut it into 2×2×2cm cube blocks by wood cutting machine and physical grinding. Prepare two different concentrations of sodium hydroxide solutions of 1% (w / v) and 5% (w / v), transfer the prepared sodium hydroxide solutions to the polytetrafluoroethylene lining of 100mL hydrothermal reactors, and then put a treated fresh and healthy pine wood in each. Place the assembled hydrothermal reactor in a forced air drying oven and heat it to 180℃ for 10h, wait for it to cool naturally to room temperature, take out the wood blocks and wash them repeatedly with deionized water until the solution becomes neutral, and finally obtain aged wood with two different moisture contents, moderately degraded and severely degraded. The moisture content of the moderately degraded pine wood blocks is 180%~300%, and the moisture content of the severely degraded pine wood blocks is >300%.

[0020] Two kinds of pine wood with different degradation degrees, moderate degradation and severe degradation, were artificially prepared by the hydrothermal method. The moisture content, main chemical components, etc. were measured by Fourier infrared spectroscopy, XRD and other methods to characterize their degradation degrees, and their sizes and surface morphologies were observed using super depth of field.

[0021] Reference Figure 1 This is a comparison of fresh pine wood and pine wood after hydrothermal degradation. It can be found that the color of pine wood turns dark brown after hydrothermal treatment.

[0022] Reference Figure 2 Ultra-depth comparison of pine wood with different degrees of hydrothermal degradation.

[0023] Reference Figure 3 Comparison of SEM images of pine wood with different degrees of hydrothermal degradation. The surface of pine wood becomes rougher with increasing alkali concentration.

[0024] Reference Figure 4 FTIR spectra of pine wood treated by hydrothermal degradation and 85℃ water bath. 1038cm -1 The left and right absorption peaks are the bending vibrations of the CH bonds of lignin; 1500cm -1 Nearby is the absorption peak of the lignin benzene ring skeleton; 892cm -1 The absorption peak at 3399cm is mainly the CH bending vibration of cellulose; -1 The broad peak is the stretching vibration of -OH. Under 5% NaOH hydrothermal treatment, the absorption peaks of lignin and cellulose basically do not exist, which shows that alkali has a great influence on the degradation of the main chemical components of wood.

[0025] Reference Figure 5The XRD spectra of pine wood treated by hydrothermal degradation and 85℃ water bath treatment. Compared with the sample immersed in pure water at 85℃, the peaks of 101, 002, and 040 decreased significantly, the crystalline cellulose content decreased, and the alkali concentration increased from 1% to 5%, and the peaks of 101, 002, and 040 also decreased slightly. In addition, compared with pure water at 85℃ and pure water hydrothermal for 10h, the 002 peak is almost the same, and the influence of temperature and pressure is sensitive to the 101 and 040 crystal planes.

[0026] Example 1 Step 1, reinforcement treatment of pine wood with different degradation degrees with menthol: Use menthol from Sinopharm Reagent as a temporary reinforcement agent to reinforce pine wood blocks with different degradation degrees. First, place 2g of the reinforcement agent in a beaker and melt it in a water bath. The water bath temperature is maintained at about 85°C until the menthol and its derivatives are completely melted. Wrap the prepared artificially aged pine wood samples with moderate and severe degradation degrees with gauze / fiber fabric, then use a plastic dropper to absorb about 2mL of the reinforcement agent and evenly drop it on the wrapping. Menthol evenly penetrates into the wood block through the wrapping. Wait for a few minutes for the menthol to solidify until the wrapping and the wood sample are tightly bonded together and can be taken and placed at will, indicating that menthol plays a temporary solidifying role, and reinforced moderate and severe degradation samples are obtained.

[0027] Step 2, removal of menthol: The reinforced samples with different degradation degrees obtained in step 1 are desoldered, and absorbent cotton soaked in anhydrous ethanol is covered on the reinforced samples obtained in step 1. The absorbent cotton soaked in anhydrous ethanol is replaced once every hour on average. In the interval between replacing the absorbent cotton, the sample is sprayed with water until the original state of the wood is restored and the reinforcing agent is completely removed when the covering falls off naturally, thereby obtaining a comparison sample block from which the reinforcing agent has been removed.

[0028] The reinforcing agent menthol was used for temporary reinforcement treatment, and the moderately degraded pine wood blocks and severely degraded pine wood blocks after the reinforcement was removed were observed using super depth of field. The dimensional changes and surface morphologies before and after reinforcement were compared, and the reinforcement and protection effects of pine wood with different degrees of degradation were evaluated.

[0029] Example 2 Step 1, reinforcement treatment of pine wood with different degradation degrees by menthol; Menthol purchased from Sinopharm Reagent was used as a temporary reinforcement agent to reinforce pine blocks with different degrees of degradation. First, 2g of the reinforcement agent was placed in a beaker and melted by heating in a water bath. The water bath temperature was maintained at about 85°C until the menthol and its derivatives were completely melted. The artificially aged pine samples with moderate and severe degradation were prepared by wrapping them with gauze / fiber fabric, and then about 5mL of the reinforcement agent was evenly dripped onto the wrapping with a plastic dropper. The menthol evenly penetrated into the wood block through the wrapping. After waiting for a few minutes, the menthol solidified until the wrapping and the wood sample were tightly bonded together and could be taken and placed at will, indicating that the menthol played a temporary solidifying role, and the reinforced moderate and severe degradation samples were obtained.

[0030] Step 2, removal of menthol; The reinforced samples with different degradation degrees obtained in step 1 are desoldered. The reinforced samples obtained in step 1 are covered with absorbent cotton soaked in anhydrous ethanol. The absorbent cotton soaked in anhydrous ethanol is replaced once an hour on average. In the interval between replacing the absorbent cotton, the samples are sprayed with water until the original state of the wood is restored. When the covering falls off naturally, the reinforcing agent is completely removed, thereby obtaining a comparison sample block from which the reinforcing agent has been removed.

[0031] The reinforcing agent menthol was used for temporary reinforcement treatment, and the moderately degraded pine wood blocks and severely degraded pine wood blocks after the reinforcement was removed were observed using super depth of field. The dimensional changes and surface morphologies before and after reinforcement were compared, and the reinforcement and protection effects of pine wood with different degrees of degradation were evaluated.

[0032] Example 3 Step 1, reinforcement treatment of pine wood with different degrees of degradation by menthyl lactate: Menthyl lactate of Sinopharm Reagent is used as a temporary reinforcement agent to reinforce the prepared moderately degraded and severely degraded pine wood block targets. First, 2g of the reinforcement agent is placed in a beaker and melted by water bath heating. The water bath temperature is maintained at about 85°C until menthol and its derivatives are completely melted. The prepared artificially aged pine wood samples with moderate and severe degradation are covered with gauze / fiber fabric, and then about 2mL of the reinforcement agent is drawn with a plastic dropper and evenly added to the covering. Menthyl lactate evenly penetrates into the wood block through the covering. After waiting for a few minutes, the menthyl lactate solidifies until the covering and the wood sample are tightly bonded together and can be taken and placed at will, indicating that menthyl lactate plays a temporary solidifying role, and reinforced moderately degraded and severely degraded samples are obtained.

[0033] Step 2, removal of menthyl lactate; The reinforced samples with different degradation degrees obtained in step 1 are desoldered, and absorbent cotton soaked in anhydrous ethanol is covered on the reinforced samples obtained in step 1. The absorbent cotton soaked in anhydrous ethanol is replaced once every hour on average. In the interval between replacing the absorbent cotton, the sample is sprayed with water until the original state of the wood is restored and the reinforcing agent is completely removed when the covering falls off naturally, thereby obtaining a comparison sample block from which the reinforcing agent has been removed.

[0034] The reinforcing agent menthol was used for temporary reinforcement treatment, and the moderately degraded pine wood blocks and severely degraded pine wood blocks after the reinforcement was removed were observed using super depth of field. The dimensional changes and surface morphologies before and after reinforcement were compared, and the reinforcement and protection effects of pine wood with different degrees of degradation were evaluated.

[0035] Example 4 Step 1, reinforcement treatment of pine wood with different degradation degrees by menthyl lactate; Menthyl lactate from Sinopharm Reagent was used as a temporary reinforcement agent to reinforce the prepared moderately degraded and severely degraded pine blocks. First, 2g of the reinforcement agent was placed in a beaker and melted by water bath heating. The water bath temperature was maintained at about 85°C until menthol and its derivatives were completely melted. The artificially aged pine samples with moderate and severe degradation were wrapped with gauze / fiber fabric, and then about 5mL of the reinforcement agent was drawn with a plastic dropper and evenly added to the wrapping. Menthyl lactate evenly penetrated into the wood block through the wrapping. After waiting for a few minutes, the menthyl lactate solidified until the wrapping and the wood sample were tightly bonded together and could be taken and placed at will, indicating that menthyl lactate played a temporary solidifying role, and the reinforced moderately degraded and severely degraded samples were obtained.

[0036] Step 2, removal of menthyl lactate: The reinforced samples with different degradation degrees obtained in step 1 are desoldered, and absorbent cotton soaked in anhydrous ethanol is covered on the reinforced samples obtained in step 1. The absorbent cotton soaked in anhydrous ethanol is replaced once every hour on average. In the interval between replacing the absorbent cotton, the sample is sprayed with water until the original state of the wood is restored and the reinforcing agent is completely removed when the covering falls off naturally, thereby obtaining a comparison sample block from which the reinforcing agent has been removed.

[0037] The reinforcing agent menthol was used for temporary reinforcement treatment, and the moderately degraded pine wood blocks and severely degraded pine wood blocks after the reinforcement was removed were observed using super depth of field. The dimensional changes and surface morphologies before and after reinforcement were compared, and the reinforcement and protection effects of pine wood with different degrees of degradation were evaluated.

[0038] Effect example Reference Figure 6The following are the comparison pictures of the super depth of field in the tangential direction of the pine wood samples after reinforcement and drying. a) and d) are the super depth of field in the tangential direction of the original fresh pine wood samples, b) is the super depth of field picture in the tangential direction of the pine wood after the reinforcement and removal of menthyl lactate, c) is the super depth of field picture in the tangential direction after the reinforcement and removal of menthyl lactate and drying, e) is the super depth of field picture in the tangential direction after the reinforcement and removal of menthol, and f) is the super depth of field picture in the tangential direction after the reinforcement and removal of menthol and drying. By comparison, it can be seen that there is no obvious color and volume change in the sample in the tangential direction, which proves that the two reinforcement agents have a good protective effect on pine wood.

[0039] Reference Figure 7 The figure shows the reinforcement and removal process of water-saturated pine wood. In the whole process, a) is water-saturated aged wood, b) the aged wood is wrapped with gauze, and then heated in a water bath to melt the reinforcing agent, and the reinforcing agent is evenly dropped on the surface of the gauze with a dropper as shown in c), so that the reinforcing agent is evenly infiltrated into the water-saturated aged sample, and then the reinforcing agent is waited for to solidify as shown in d), and the reinforcing agent is removed after solidification as shown in e), and finally the sample after removal is successfully obtained as shown in f).

[0040] Reference Figure 8 Comparison of 1% NaOH hydrothermal aging pine wood samples before and after reinforcement. a) and c) are pictures of 1% NaOH hydrothermal aging samples before reinforcement, b) is a picture of 1% NaOH hydrothermal aging samples reinforced with menthyl lactate, and d) is a picture of 1% NaOH hydrothermal aging samples reinforced with menthol. Fig. 9 The following are comparisons of pine wood samples aged with 5% NaOH before and after reinforcement. a) and c) are pictures of 5% NaOH hydrothermal aged samples before reinforcement, b) is a picture of 5% NaOH hydrothermal aged samples reinforced with menthyl lactate, and d) is a picture of 5% NaOH hydrothermal aged samples reinforced with menthol. Comparing the pictures, it can be seen that the morphology does not change much after the reinforcement is removed, and there is no cracking or slag phenomenon, indicating that both reinforcement agents have a temporary reinforcement effect.

[0041] Experiments have shown that menthol, as a temporary reinforcement agent, has strong penetration ability and good reinforcement effect. After reinforcing the cultural relics, it can be naturally removed as it evaporates, leaving no harmful residues. It has high safety, low cost and a wide range of applications.

[0042] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A temporary reinforcement method for wooden cultural relics using menthol and its derivatives, characterized in that: The steps include: (1) Preparing wood substrates with different degradation degrees: cutting wood blocks, soaking the cut wood blocks in an alkaline solution, heating and keeping them warm, and then cooling them to room temperature for washing; (2) Reinforcement treatment of wood substrates with different degradation degrees using menthol or menthol derivatives as reinforcing agents: Wrapping the wood substrate obtained in step (1) with fiber fabric, applying a molten curing agent to the wrapped wood substrate, and obtaining a reinforced wood substrate sample after standing; (3) Removal of the reinforcing agent on the wood matrix: Cover the sample with cotton wool soaked in anhydrous ethanol, and keep replacing the cotton wool to allow the anhydrous ethanol to continue to penetrate the sample. During this period, the sample is hydrated until the reinforcing agent is completely removed.

2. The temporary reinforcement method for wooden cultural relics using menthol and its derivatives according to claim 1, characterized in that: In the step (1), the reaction system is placed in a heating chamber for heating, and the temperature in the heating chamber is raised to 170-190° C. and maintained for 8-12 hours.

3. The temporary reinforcement method for wooden cultural relics using menthol and its derivatives according to claim 1, characterized in that: The alkaline solution described in step (1) is a sodium hydroxide solution.

4. The temporary reinforcement method for wooden cultural relics using menthol and its derivatives according to claim 1, characterized in that: The mass concentration of the alkaline solution in step (1) is 1-5%.

5. The temporary reinforcement method for wooden cultural relics using menthol and its derivatives according to claim 1, characterized in that: In step (1), the wooden block is cut into cubes of 2×2×2 cm.

6. The temporary reinforcement method for wooden cultural relics using menthol and its derivatives according to claim 1, characterized in that: The menthol derivative in step (2) is menthyl lactate.

7. The temporary reinforcement method for wooden cultural relics using menthol and its derivatives according to claim 1, characterized in that: The application method in step (2) is any one of dripping, spraying, and pouring.

8. The temporary reinforcement method for wooden cultural relics using menthol and its derivatives according to claim 1, characterized in that: In step (3), water replenishment is performed by any one or more of spraying, steaming or immersing.

9. Application of the temporary reinforcement method for wooden cultural relics using menthol and its derivatives according to any one of claims 1 to 8 in the field of reinforcement of wooden cultural relics.

Citation Information

Patent Citations

  • Cotton fiber silk net reinforcement method for fragile paper

    CN103485240A

  • Menthol derivatives, mixture thereof, and preparation method and applications of menthol derivatives

    CN108610257A

  • Temporary sealing and protecting method for cultural relics at archaeological excavation site

    CN108864789A

  • Method for temporary reinforcement of cultural relics

    CN110067156A